(untitled) (FUDMA JOURNAL OF SCIENCES, 2020)
The Human Immunodeficiency Virus (HIV) and Acquired Immunodeficiency Syndrome (AIDS) remains a public health crisis that has contributed to the majority of deaths recorded in the past decade, affecting Nigeria and other countries of the world as it has become drug resistance in some patients. This study was aimed at estimating the effects of covariates on the survival time for HIV/AIDS patients using the Cox PH model. The KM results indicated that 91 patients were males, out of which 31 experienced the event of interest, and 60 (68.9%) were censored, 209 were females, 65 died due to AIDS, and 144 were censored (68.9%) respectively. The results of the Cox PHM indicated that sex, age, and health of patients are positively associated with death due to AIDS with the associated negative length of survival for HIV/AIDS patients with HR (1.149, 1.235, 1.887, and 1.306) respectively. The study concluded that CD4 cell counts are the only variable or covariate that showed a lower risk of death due to AIDS. The results further stated that patients with high CD4 cell counts have lower risks of death due to AIDS but an increase in survival time considering other factors. The study, therefore recommends that survival analysis should be used to assess the various risk factors and the confounding effects associated with them stressing that a patient’s lifestyle should be improved to live healthy as they continue to age older.